Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/mi.2013.92
|View full text |Cite
|
Sign up to set email alerts
|

TNF superfamily member TL1A elicits type 2 innate lymphoid cells at mucosal barriers

Abstract: Immune responses at mucosal barriers are regulated by innate type 2 lymphoid cells (ILC2s) that elaborate effector cytokines interleukins 5 and 13 (IL5 and IL13). IL25 and IL33 are key cytokines that support ILC2s; however, mice deficient in these pathways retain some functional ILC2s. Analysis of human and murine cells revealed that ILC2s highly express tumor necrosis factor (TNF)-receptor superfamily member DR3 (TNFRSF25). Engagement of DR3 with cognate ligand TL1A promoted ILC2 expansion, survival, and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
169
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(172 citation statements)
references
References 39 publications
3
169
0
Order By: Relevance
“…Polymorphisms in the TNFSF15 gene, encoding TL1A, also associate with rheumatoid arthritis and inflammatory bowel disease. ILC2 express DR3, and treatment with TL1A resulted in ILC2 proliferation and their expression of IL-5 in vitro (65,66) and in vivo (66). This response was enhanced in the presence of IL-7 but was an order of magnitude below that induced by IL-33.…”
Section: Ilc2 In Lung Allergy and Inflammationmentioning
confidence: 91%
See 2 more Smart Citations
“…Polymorphisms in the TNFSF15 gene, encoding TL1A, also associate with rheumatoid arthritis and inflammatory bowel disease. ILC2 express DR3, and treatment with TL1A resulted in ILC2 proliferation and their expression of IL-5 in vitro (65,66) and in vivo (66). This response was enhanced in the presence of IL-7 but was an order of magnitude below that induced by IL-33.…”
Section: Ilc2 In Lung Allergy and Inflammationmentioning
confidence: 91%
“…ILC2 numbers were reduced in the lungs and BAL of DR3 2/2 mice, as compared with control mice, and this correlated with decreased inflammation (65,66). This effect was not due solely to the role of TL1A on T cells, because DR3 2/2 Rag2 2/2 mice also had fewer ILC2, but these data may also suggest that DR3 signaling in T cells is required to regulate ILC2 numbers (66). Notably, human ILC2 also express DR3 and respond to TL1A.…”
Section: Ilc2 In Lung Allergy and Inflammationmentioning
confidence: 98%
See 1 more Smart Citation
“…Beyond epithelial cell -derived cytokine regulation, ILC2 activation and migration also appear to be regulated by other factors, such as TL1A (Yu et al 2013;Meylan et al 2014) and eicosanoids (Barnig et al 2013;Chang et al 2013;Doherty et al 2013;Xue et al 2013) in the intestine and lung, respectively. In the intestine, VIP, which is heavily influenced by caloric intake and circadian rhythms, has also been shown to activate cytokine production from ILC2s .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, LXA 4 in conjunction with other proresolving receptors such as CMKLR1 was found to be expressed on human ILC2s, suggesting that these anti-inflammatory pathways may be operative on ILC2s (Barnig et al 2013). Finally, two groups independently identified that the TNF-family cytokine TL1A promotes allergic airway inflammation and pathology in response to papain (Yu et al 2013;Meylan et al 2014), and that human peripheral blood ILC2s are activated by TL1A in synergy with IL-25 and IL-33 (Yu et al 2013). These studies indicate that various epithelial cellderived cytokines might coordinately regulate ILC2 phenotype and function in inflamed tissue in conjunction with eicosinoids and TL1A.…”
Section: Ilc2s and Allergic Airway Inflammationmentioning
confidence: 99%